Lichens and Microplastics - ÖZBEY, Nida Nur; YILDIZ, Atila (Turkey Health Literacy Journal, 2025)
Lichens are composed of the physiological and morphological associations of algae and fungi. The secondary metabolites within lichens enable them to survive even in extreme conditions and adapt to environmental factors. Secondary metabolites confer biological activities such as antimicrobial, antibacterial, and antifungal properties on lichens. Lichens have numerous applications. From past to present, they have been used in alternative medicine, food, industry, and biomonitoring. The increasing harm caused by microplastics, which are quite small in size, to nature and humans has led to the need to focus on research in this area. Passive biomonitoring of microplastic levels in the air was conducted using various lichen species, particularly the Xanthoria parietina lichen. Microplastic residues were detected in the lichens examined using this method.
Keywords: Microplastic; Pollution; Lichen; Health